Galantamine potentiates the neuroprotective effect of memantine against NMDA-induced excitotoxicity - Lopes, João P (Blackwell Publishing Ltd, 2013)
The combination of memantine, an N-methyl-d-aspartate (NMDA) receptor antagonist, with an acetylcholinesterase inhibitor (AChEI) is the current standard of care in Alzheimer's disease (AD). Galantamine, an AChEI currently marketed for the treatment of AD, exerts memory-enhancing and neuroprotective effects via activation of nicotinic acetylcholine receptors (nAChRs). Here, we investigated the neuroprotective properties of galantamine in primary cultures of rat cortical neurons when given alone or in combination with memantine. In agreement with previous findings, we found that memantine was fully effective in reversing NMDA toxicity at concentrations of 2.5 and 5 μmol/L. Galantamine also completely reversed NMDA toxicity at a concentration of 5 μmol/L. The α7 and α4β2 nAChR antagonists, methyllycaconitine, and dihydro-β-erythroidine blocked the neuroprotective effect of galantamine, demonstrating the involvement of nAChRs. The combination of memantine with galantamine produced synergistic actions, such that full neuroprotective efficacy, was obtained at inactive concentrations of memantine (0.1 μmol/L) and galantamine (1 μmol/L). A similar potentiation was also observed when memantine was replaced with ifenprodil, suggesting a possible involvement of the NR2B subunit of the NMDA receptor. In summary, our study reports for the first time at a cellular level that memantine and galantamine interact on the same excitotoxic cascade and that the combination of these two drugs can result in a remarkable neuroprotective effect.